Effect of light wavelengths on the non-polar InGaN-based thin film solar cells performances using one-dimensional modeling - Madi, Lourassi (Elsevier, 2019)
In the present contribution, we determine the effect of light wavelength variation on the performances of the non-polar InGaN-based solar cells in order to find the optimum light wavelength that yields a high efficiency. The calculations are performed using a one-dimensional SCAPS-1D tool (One-Dimensional Solar Cell Capacitance Simulator). The simulation has been carried out by lighting through a n- In0.3Ga0.7As layer. An efficiency of 12.24% with the fill-factor FF ¼ 51.35%, open-circuit voltage VOC ¼ 0.72 V and short-circuit current density JSC ¼ 32.80 mA/cm2 is obtained under AM1.5G illumination. The quantum efficiency characteristic displays a maximum value of more than 90% in the visible range using AM1.5G illumination. Moreover, our results show that with increasing light wavelengths from the blue light (around 450 nm) to the end of the red light (around 700 nm), the efficiency increases from 13.76% to above of 20%. The short-circuit current density is also increased from 37.33 mA/cm2 to 53.81 mA/cm2 with increasing light wavelengths from 450 nm to 700 nm. However, the variation of the light wavelength seems to have only a small influence on the open-circuit voltage and fill-factor. The present study provides information about the properties of the materials used in the cell structure of efficient InGaN solar cells